SIX-MONTH OUTCOMES IN ACUTE CORONARY SYNDROME PATIENTS INCLUDED IN THE REGISTRY RECORD-3 - A. D. Erlikh (Российский кардиологический журнал, 2017)
Erlikh A. D. on behalf of the RECORD-3* working teamAim. Evaluation of 6-month observation of acute coronary syndrome (ACS) patients included into the ACS registry RECORD-3.Material and methods. To the registry RECORD-3, all ACS patients were being included if hospitalized during 1 month in 2015 (march-april) in 47 centers among 37 Russia cities. Follow-up lasted for 6 months with telephone calls, in 35 centers.Results. Among all participants (n=2370), 6-month outcomes were collected in 1433 (64%). By most demographic, anamestic and clinical characteristics the group of those failed to collect data was comparable with the others. Frequency of fatal outcomes after discharge in 6 months post ACS was 4,2%, new myocardial infarction (MI) — 3,2%, stroke — 0,7%. Frequency of combination events (death+MI), death+ MI+stroke reached 5,7% and 8,5%, respectively. Coronary intervention in 6 months was done in 12,0% (2/3 underwent PCI, 1/3 — bypass surgery). In 19% cases the intervention was urgent. There were no statistically significant differences by the prevalence of adverse events and bypass surgery among those with diagnosed MI in-patient and non-MI, as between ACS with ST elevation (STEACS) or no (NSTEACS), excluding the prevalence of fatal outcomes: 2,8% in STEACS and 5,0% in NSTEACS (p=0,038). The grade of frequency decline of prescribed medication intake by 6 months reached 12% for aspirin, 29% for clopidogrel, 33% for ticagrelor, 29% for oral anticoagulants, 28 for ACEi/ARB, 19% for beta-blockers, 21% for statins.Conclusion. By multifactorial regression analysis, the independent predictors of fatal outcomes were found, that developed in 6 months post discharge.